The Influence of Utilizing Gamification Media Wordwall on the Improvement of Pancasila Education Learning Outcomes - Rahmasari, Riska; Murdiono, Mukhamad; Sunarso, Sunarso (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This research aims to investigate the impact of using wordwall gamification media on enhancing educational achievements. The research strategy used in this study was the One-Group pretest-posttest design. The participants consisted of 43 students enrolled in the Chemistry C Education program at Yogyakarta State University, taking the Pancasila Education course. The data collected from the study were analyzed using descriptive statistics. According to the findings of inferential statistical analysis using the t-test method, there was a significant improvement in students' learning outcomes, with a mean gain of 12.31 score points. Given that the t count is statistically significant at a significance level of 0.05, the null hypothesis (H0) is rejected in favor of 3400 of the alternative hypothesis (Ha). This implies a discernible impact of using wordwall gamification media on enhancing learning outcomes. Based on the findings and deliberations, it can be deduced that the utilization of Wordwall media in the context of gamified learning exhibits efficacy in enhancing the educational achievements of 43 participants enrolled in the C Chemical Education program, namely those doing Pancasila Education courses at Yogyakarta State University.